The role of librarybibliographical knowledge propoganda for Vilnius higher party school students in getting information - Тамошюнас, Леонас (Knygotyra, 1981)
This article maintains that improving of information supply of study process in V. H. P. S. is carried on the base of wide usage of library stock. It has been got by propaganda of librarybibliographical knowledge and individual work with the book. Here in V. H. P. S. we have got regularly classes on methods of individual work with the book for the first year students. The educational programme has been made in accordance with a system of librarybibliographical classes. Good experience of higher schools in our country has been used here particularly. The experience of work with the students of Vilnius Kapsukas State University in first place. The information of this programme is devoted. to general acquaintance with the importance of individual work, the role of book, library and bibliography in educational process.The first part of the programme coveres the questions of publication of social-political books. The second part is devoted to the search of information needed. The third part coveres the questions of scientific organization of intellectual work and culture of reading of the students.Great attention is paid to practical classes, when students find information themselves. This programme gives a list of books which should help the students to enrich their knowledge on this or that subject. In school library individual consultations are carried on, when listeners have possibility to pay great attention to the particular questions connected with the subject. Except oral means of propaganda, mentioned above, there are some forms of visual propaganda of librarybibliographical knowledge exibitions of books and placards on individual work methods. Free access to inquiry bibliographical machinary has been organized well in the library. And we pay also great attention to careful mounting of catalogues and card indexes.